Comparison of an ELISA assay for the detection of adhesive/invasive Neospora caninumtachyzoites - Pereira,Luiz Miguel (2014)
Neospora caninum belongs to the phylum Apicomplexa, the causative agent of neosporosis, which leads to economic impacts on cattle production. A common feature among apicomplexan parasites is the invasive process driven mostly by the parasite. As a first evaluation of candidate molecules that play a possible role by interfering in this invasive process, the in vitro invasion assay is a fast and direct way to screen future agonists or antagonists. This work involved the development of a new cell culture ELISA and transient β-galactosidase activity applied to the semi-quantitative detection of N. caninum in Vero cell culture. Cell culture ELISA is based on histochemistry and immunology, resulting in a colorimetric reaction. The β-galactosidase activity was obtained by the transient transfection of the lacZ gene under control of RPS13 promoter of N. caninum. These methods were used to evaluate the effects of temperature (37°C and 85°C) on the invasion and adhesion of tachyzoites. The three tested methods (real time PCR, β-galactosidase activity and ELISA) showed a similar pattern, indicating that different methods may be complementary.